Psoriasis and Pregnancy: Retrospective Evaluation of 47 Pregnancies in a Tertiary Center - Tanacan, Efsun; Tanacan, Atakan; Fadiloglu, Erdem; Unal, Canan; Beksac, Mehmet Sinan (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: To evaluate the impact of psoriasis on pregnancy outcomes. Study Design: Data of pregnant women with chronic plaque psoriasis who were followed up at Hacettepe University Hospital between January 1, 2010 and December 31, 2017 were evaluated. Pregnant women with singleton pregnancies who had chronic plaque psoriasis were included in the study. Patients were divided into two groups based on the clinical course of psoriasis: group 1 (improvement/disease-stable), and group 2 (deterioration). Median maternal age, gravida, parity, gestational week at birth, birthweight, 5th minute APGAR score together with the rates of cesarean section, neonatal intensive care unit admission and pregnancy complications (spontaneous abortion, preterm delivery, fetal growth restriction and preeclampsia) were compared between the groups. Results: There were 29 (61.7%) patients in group 1 and 18 (38.3%) patients in group 2. Mean values for maternal age, gravida and parity were comparable between the groups (p values were 0.32, 0.09 and 0.17, respectively). Median values for gestational week at birth (39.2 vs 36.1, p =0.002), birthweight (3200 vs 2310, p =0.002) and 5th minute APGAR score (9 vs 7, p <0.001) were statistically significantly lower in group 2. Cesarean section (33.3% vs 71.4%, p =0.02), neonatal intensive care unit admission (11.1% vs 64.3%, p <0.001) and pregnancy complication rates (p =0.003) were statistically significantly higher in group 2. Frequencies of spontaneous abortion, preterm delivery, fetal growth restriction and preeclampsia were 6.9%, 10.3%, 3.4% and 3.4% in group 1, and 22.2%, 27.8%, 16.7% and 16.7% in group 2, respectively. Conclusion: Deterioration of psoriasis in pregnancy was associated with adverse obstetric outcome.